How Classroom Climate, Student Problem Behaviors, and Collective Teacher Efficacy Relate to SWPBIS Implementation Fidelity in 23 Swedish Schools - Martin Karlberg (Education Sciences)
This study explores factors influencing the implementation fidelity of the School-Wide Positive Behavior Interventions and Supports (SWPBIS) program, adapted as Inclusive Behavioral Support in Schools (IBIS) in Sweden. The objective was to investigate how classroom climate, student problem behaviors, and collective teacher efficacy relate to the program’s implementation fidelity across 23 Swedish schools. A total of 653 school personnel participated, completing surveys on classroom climate, problem behaviors, and collective efficacy. The Benchmark of Quality (BoQ) was used to assess implementation fidelity after seven months. Chi-square analyses revealed no significant association between program fidelity and student problem behaviors at either the classroom or school level. Similarly, no significant relationship was found with collective teacher efficacy. Interestingly, a significant association emerged between poor classroom climate at baseline and higher implementation fidelity, suggesting that schools facing greater challenges may engage more rigorously with the program to address pressing issues. These findings underscore the complexity of implementation processes and highlight the importance of contextual factors, particularly classroom climate, in influencing the successful adoption of evidence-based interventions in educational settings. These findings provide valuable insights for educators and policymakers, emphasizing the need to consider classroom climate when implementing evidence-based interventions like SWPBIS, ultimately supporting more effective and sustainable positive behavior programs in schools.